2020
DOI: 10.1097/mnm.0000000000001157
|View full text |Cite
|
Sign up to set email alerts
|

Complementary role of 18F-FDG PET/CT for sentinel lymph node algorithm in endometrial cancer with high-risk factors for lymphatic metastasis

Abstract: Objective National Comprehensive Cancer Network (NCCN) sentinel lymph node (SLN) algorithm includes ‘mandatory steps’ for evaluating pelvic lymph nodes, but assessment of paraaortic area is left to surgeon’s discretion. In this study, we aimed to investigate the complementary role of preoperative 18F-FDG PET/computed tomography (CT) scan in detecting pelvic and especially paraaortic lymphatic metastasis in endometrial cancer patients with high-risk factor(s) according to Mayo Clinic Criteria and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Researchers from Korea showed that a sequential administration of bilateral uterine cornus injection of ICG followed by cervical injection, improved the para-aortic SLN detection rate from 5.7% to 38.2% in upper para-aortic area (p<0.001) and 18.7% to 67.1% in lower para-aortic area (p<0.001), which in turn identified more metastatic SLN in aortic area (7.9% vs. 2.4%) (p=0.070) ( 157 ). Researchers from Italy and Turkey suggest the addition of preoperative PET-CT in favor of PALAD decision ( 111 , 113 , 158 ). Taskin included 38 high-risk patients.…”
Section: Controversial Issuesmentioning
confidence: 99%
“…Researchers from Korea showed that a sequential administration of bilateral uterine cornus injection of ICG followed by cervical injection, improved the para-aortic SLN detection rate from 5.7% to 38.2% in upper para-aortic area (p<0.001) and 18.7% to 67.1% in lower para-aortic area (p<0.001), which in turn identified more metastatic SLN in aortic area (7.9% vs. 2.4%) (p=0.070) ( 157 ). Researchers from Italy and Turkey suggest the addition of preoperative PET-CT in favor of PALAD decision ( 111 , 113 , 158 ). Taskin included 38 high-risk patients.…”
Section: Controversial Issuesmentioning
confidence: 99%
“…Taskin et al recently evaluated the complementary role of PET/CT in the sentinel lymph node algorithm in high-risk patients. In their study of 38 patients, two out of 10 patients with lymph node metastases had isolated paraaortic metastases diagnosed only on PET/CT [31].…”
Section: Discussionmentioning
confidence: 98%
“…The incidence of para-aortic metastases is 51% when pelvic lymph nodes are positive, but it dramatically decreases to 3% when pelvic lymph nodes are negative ( 61 ). Some authors have proposed the implementation of PET-CT in the preoperative set-up for the assessment of the para-aortic space ( 105 , 106 ), however the survival benefit from para-aortic lymphadenectomy remains controversial. The above-mentioned problem for the SLN in the para-aortic space could be addressed by using other tracer injections sites or a combination of them.…”
Section: Lymph Nose Assessmentmentioning
confidence: 99%